2020
DOI: 10.1016/j.dib.2020.105959
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation: Data on effects of titanium dioxide nanoparticles on phytoremediation of antimony polluted soil

Abstract: This data article presents effects of titanium dioxide nanoparticles (TiO 2 NPs) on phytoremediation of antimony contaminated soil using S. Bicolor in detail. Seedlings of S. bicolor were exposed to different doses of TiO 2 NPs (0,50,100,250,500 and 1000 mg/kg) in plastic pots containing Sb-contaminated soil and cultivated over a 80-day period in a greenhouse. Harvested plants were dried in an oven at 70 °C for 48 h to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…When the test plant was exposed to 500 mg/kg of Sb, 672.8 mg Sb/kg were accumulated in the plant while when the initial concentration was 1000 mg/kg, the plant uptake was estimated 2054.8 mg Sb/kg [ 21 ]. Seedlings of S. bicolor in Sb-contaminated soil were treated with different levels of TiO 2 nanoparticles and the results showed that the bioconcentration factor was above one for each treatment, indicating that this plant also has phytoremediation potential [ 22 ]. To date, the mechanism of Sb accumulation in plants is not well understood and there is need for in-depth studies.…”
Section: Introductionmentioning
confidence: 99%
“…When the test plant was exposed to 500 mg/kg of Sb, 672.8 mg Sb/kg were accumulated in the plant while when the initial concentration was 1000 mg/kg, the plant uptake was estimated 2054.8 mg Sb/kg [ 21 ]. Seedlings of S. bicolor in Sb-contaminated soil were treated with different levels of TiO 2 nanoparticles and the results showed that the bioconcentration factor was above one for each treatment, indicating that this plant also has phytoremediation potential [ 22 ]. To date, the mechanism of Sb accumulation in plants is not well understood and there is need for in-depth studies.…”
Section: Introductionmentioning
confidence: 99%
“…The latter facilitates the formation of a hydrogel systemwhich assists with the retention of urea within CRUs and subsequent slower release of ureafollowing absorption of water by the urea–MPN matrix from soil. ,, Moreover, the heated urea–MPN Fe , used as a model, showed a lower mechanical resistance than heated urea–MPN Ti and urea–MPN Zr , making it less stable in soil and exhibiting a faster urea release rate. It is noted that the metal–phenolic structure can undergo degradation in soil, resulting in the release of metals. ,, Zr and Ti are naturally occurring elements that are considered to have low toxicity and are commonly found in soils. , The concentration of Zr or Ti elements used in the urea–MPN 40% matrices is approximately 1 wt % (equivalent to ∼20 mg per kg of soil), which is lower than the concentration at which these elements are naturally present in soil. …”
Section: Resultsmentioning
confidence: 99%
“…It is noted that the metal−phenolic structure can undergo degradation in soil, resulting in the release of metals. 46,76,77 Zr and Ti are naturally occurring elements that are considered to have low toxicity and are commonly found in soils. 78,79 The concentration of Zr or Ti elements used in the urea−MPN 40% matrices is approximately 1 wt % (equivalent to ∼20 mg per kg of soil), which is lower than the concentration at which these elements are naturally present in soil.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…They found that a significant amount of Sb was taken by plants grown under Sb stress. Similarly, sorghum plants grown under Sb also showed a significant increase in Sb accumulation in roots and the translocation of sorghum plants ( Müller et al., 2013 ; Zand and Heir, 2020 ; Zand et al., 2020 ). Translocation factor >1 is considered a good indicator of phytoremediation ( Antoniadis et al., 2021 ).…”
Section: Phytoremediation and Microbial Remediation Of Sb-contaminate...mentioning
confidence: 99%
“…(2020) studied the impact of titanium dioxide (TiO 2 ) nanoparticles and sorghum bicolor on the remediation of Sb-contaminated soil. They found that TiO 2 nanoparticles (0–1000 mg/kg) substantially improved biomass productivity and reduced Sb uptake and translocation ( Zand and Heir, 2020 ). In another study, Zand et al.…”
Section: Use Of Plant Additives To Reduce Sb Toxicitymentioning
confidence: 99%